ATTRIBUTE ESTIMATION DEVICE, ATTRIBUTE ESTIMATION METHOD, AND PROGRAM - NAGATA HISASHI (2021)
To provide an attribute estimation device, an attribute estimation method, and a program, for estimating attributes of users for content distribution services.SOLUTION: In a server 6 for deep learning, a ranking creation processing section 61 counts, for each generation of video viewers, a play count representing a count in which a video of each video contributor is played. A learning data creation processing section 62 creates learning data to be used for deep learning of an estimation model. A deep learning-learning processing section 63 learns the estimation model by the deep leaning using the learning data created by the learning data creation processing section 62. A learning model function section 64 generates input data of the video viewers subject to generations estimation, for inputting thereof into the trained estimation model. A generation estimation function section 65 estimates generations of the video viewers based on an output result of the estimation model, for outputting an estimation result.SELECTED DRAWING: Figure 5 【課題】コンテンツ配信サービスのユーザの属性を推定する属性推定装置、属性推定方法及びプログラムを提供する。【解決手段】ディープラーニング用サーバ６において、ランキング作成処理部６１は、動画視聴者の年代別に、各動画投稿者の動画が再生された回数である再生回数を計数する。学習データ作成処理部６２は、推定モデルのディープラーニングに用いるための学習データを作成する。ディープラーニング学習処理部６３は、学習データ作成処理部６２が作成した学習データを用いてディープラーニングにより推定モデルを学習する。学習モデル機能部６４は、年代推定対象の動画視聴者の入力データを生成し、学習済みの推定モデルに入力する。年代推定機能部６５は、推定モデルの出力結果に基づいて動画視聴者の年代を推定し、推定結果を出力する。【選択図】図５